2004
DOI: 10.1590/s1519-69842004000100004
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the tegument of Metamicrocotyla macracantha (Alexander, 1954) Koratha, 1955 (Monogenea, Microcotylidae)

Abstract: The ultrastructure of the body tegument of Metamicrocotyla macracantha (Alexander, 1954) Koratha, 1955, parasite of Mugil liza from Brazil, was studied by transmission electron microscopy. The body tegument is composed of an external syncytial layer, musculature, and an inner layer containing tegumental cells. The syncytium consists of a matrix containing three types of body inclusions and mitochondria. The musculature is constituted of several layers of longitudinal and circular muscle fibers. The tegumental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…While there have been numerous previous studies focused on the morphology and ultrastructure of monogenean surface and attachment structures using TEM [10, 11, 23, 24, 26, 27, 41], none have included species from the family Diplozoidae. Highly developed transverse tegumentary annular ridges were identified on the hindbody of Eudiplozoon nipponicum using scanning electron microscopy [42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While there have been numerous previous studies focused on the morphology and ultrastructure of monogenean surface and attachment structures using TEM [10, 11, 23, 24, 26, 27, 41], none have included species from the family Diplozoidae. Highly developed transverse tegumentary annular ridges were identified on the hindbody of Eudiplozoon nipponicum using scanning electron microscopy [42].…”
Section: Discussionmentioning
confidence: 99%
“…[45]; Tetraonchoides sp. [46]; M. macracantha [11]; Dictyocotyle coeliaca [47]. In each of these, the outer syncytial layer is connected to the nucleated cell body via cytoplasmic bridges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of this is as unclear since the worm is sanguinivorous and undoubtedly derives most of its food from blood which is ingested and degraded in a well differentiated gut [26]. Suggestion about the fact that a monogenean tegument is microvillous and has an absorptive potential provide evidences of a close phylogenetic relationship between Monogenea and Cestoda, moreover, adds support to [27] argument for a close affinity between ancestral monogeneans and ancestral cestodes [22]. Postulated that the occurrence of microvilli and the absorptive function of the tegument provide evidence of a close phylogenetic relationship between Monogenea and Cestoda.…”
Section: Discussionmentioning
confidence: 94%
“…is amplified by microvilli, feature which is also characteristic of the tegument covering the adhesive areas of Diplectanum aequanus [19]. These microvilli may increase the surface area of the worm, suggesting that, on morphological grounds, the tegument has potential as a site for metabolic exchanges into and out of the worm [1,[20][21][22] and absorption of micromolecular nutrients from the surrounding environment [23] also, might support a mat of mucus that might afforded osmoregulatory or antibacterial protection [22,24]. In this way, experimental studies by [25] demonstrated that Diclidophora is capable of trans-tegumental absorption of certain neutral amino acids.…”
Section: Discussionmentioning
confidence: 99%